In vitro skin culture media influence the viability and inflammatory response of primary macrophages - Chiara Griffoni (Nature Portfolio, 2021)
Abstract The replacement of animal models for investigation of inflammation and wound healing has been advancing by means of in vitro skin equivalents with increasing levels of complexity. However, the current in vitro skin models still have a limited pre-clinical relevance due to their lack of immune cells. So far, few steps have been made towards the incorporation of immune cells into in vitro skin and the requirements for immunocompetent co-cultures remain unexplored. To establish suitable conditions for incorporating macrophages into skin models, we evaluated the effects of different media on primary keratinocytes, fibroblasts and macrophages. Skin maturation was affected by culture in macrophage medium, while macrophages showed reduced viability, altered cell morphology and decreased response to pro- and anti-inflammatory stimuli in skin differentiation media, both in 2D and 3D. The results indicate that immunocompetent skin models have specific, complex requirements for supporting an accurate detection of immune responses, which point at the identification of a suitable culture medium as a crucial pre-requisite for the development of physiologically relevant models.